Evaluation of Proopiomelanocortin (POMC) and neuropeptide Y (NPY) levels in bipolar and unipolar patients - Hatice Solak; Onur Gokcen (BMC Psychiatry)
Abstract Objective Evidence suggests that stressful life experiences contribute significantly to the aetiology of mood disorders. Hypothalamic neuropeptides are thought to be biomarkers used to differentiate patients with mood disorders. In our study, we aimed to evaluate the concentrations of hypothalamic neuropeptides NPY and POMC in patients with bipolar (BP) and unipolar (UP) depression. Methods The study included 26 UP and 28 BP patients, 27 healthy controls.NPY and POMC concentrations were quantified in peripheral blood specimens.The Hamilton Depression Rating Scale(HAM-D), Epworth Sleepiness Scale and Three-Factor Eating Questionnaire were administered. Results Serum NPY and POMC levels were significantly lower in UP and BP patients compared to the control group (p = 0.001).NPY level was lower in the depression group compared to the bipolar group but not statistically significant (p˃0.05).POMC level was decreased in the bipolar group compared to the depression group, but the results were not statistically significant (p˃0.05). No significant correlation was found between any scale score and NPY and POMC(p>0.05). Conclusion This study suggests that changes in serum NPY and POMC levels in UP and BP patients may have a potential role in disease pathophysiology. In particular, it is the first study to investigate the interaction between NPY, POMC and changes in eating behaviour in depressed patients, highlighting the need for further research in this area.